ULTRASOUND DIAGNOSIS OF NECROTIZING ENTEROCOLITIS - M. I. Pykov; V. V. Balashov; E. A. Filippova; V. Y. Bosin; Ch. M. Khizroeva (Медицинский совет, 2018)
The necrotizing enterocolitis remains the basic disease leading to a mortality of mainly prematurely born children with low and extremely low body weight. The percent of newborns with a necrotizing enterocolitis in recent years tends to increase that is connected with intensive development of a neonatology and resuscitation. The high prevalence of the necrotizing enterocolitis and the lethality accompanying it among prematurely born children remain at the high level, despite numerous researches on optimization of the principles of nursing and treatment, and in most cases meets at children at a stage of perforation of a wall of a gut and mekonialny peritonitis. Diagnostics at early stages of the begun pathological process in digestive tract at small children is extremely complicated. Recognition of precursory symptoms of a terrible disease is one of the first tasks of children’s surgeons and neonatolog. Radiodiagnosis serves as the most reliable diagnostic method at emergence of a clinical picture of a necrotizing enterocolitis. Definition of the most significant ultrasonic symptoms of a necrotizing enterocolitis remains an important task for ultrasonographers, neonatolog and children’s surgeons.